Polluting our rivers in search of gold: how sustainable are reforms to stop informal miners from returning to mining sites in Ghana? - Mensah, Albert Kobina; Tuokuu, Francis Xavier Dery (Frontiers in Environmental Science, 2023)
Introduction: Although artisanal gold mining has contributed to livelihoods in many rural communities across the world, it has destroyed and polluted several water bodies. Methods: Using Prestea in the southwestern region of Ghana, this paper demonstrates how artisanal gold mining has culminated in the pollution of freshwater bodies and the ecosystem. A non-probabilistic purposive sampling technique was used for the selection of twelve artisanal gold mining communities. We used participant observation, in-depth interviews with stakeholders, a review of policy and legal documents, reports from media websites, and site visits to various artisanal gold mining sites. We observed that artisanal gold mining has destroyed major rivers, which used to serve as major sources of water supply for domestic and irrigation purposes. To achieve benign production, the Ghanaian government over the years has made efforts to formalize the operations of galamsey activities through six main routes: policy intervention, a complete ban on their activities, military strategy, national dialogue, alternative livelihood programs, and community mining. We assessed the sustainability of three of these measures (i.e., policy intervention, a complete ban on ASM, and the military strategy). Results: We found that none of these approaches is sustainable, as the miners continue to defy the orders and military brutalities and return to mining sites to continue their operations. Conclusion: Therefore, acknowledging ASM as a significant tool for reducing poverty and its pertinent contribution to the larger economy, providing tax exemptions and incentives to informal miners to boost their production, involving local mining communities and subaltern miners in mineral governance and decision-making, removing bureaucracies and lowering costs to make the registration of new ASM businesses easier, and strengthening the mine regulatory infrastructure are necessary to formalize the sector.